Предмет: Алгебра, автор: 7tz4qe8spj

5sin2x-3sinxcosx-2cos2x>0.

Ответы

Автор ответа: daryapetrova222
0

Ответ:

Объяснение:

делим все на cos^2x: 5sin^2x/cos^2x-3sinx*cosx/cos^2x-2cos^2x/cos^2x=0

                                        5tg^2x-3tgx-2=0

Пусть tgx=y, тогда :

5y^2-3y-2=0

D= 9+40=49

y1=(3+7)/10=1

y2=(3-7)10=-2/5

обратная замена:

tgx=1                     и                              tgx=-2/5

x=П/4+Пn                                             x=arctg(-2/5)+Пn

Похожие вопросы
Предмет: Английский язык, автор: ХолоднаяДева